Facile synthesis of freestanding Si nanowire arrays by one-step template-free electro-deoxidation of SiO2 in molten salt - Ji Zhao (2013)
This communication presents a novel kind of silicon nanomaterial: freestanding Si nanowire arrays (Si NWAs), which are synthesized facilely by one-step template-free electro-deoxidation of SiO2 in molten CaCl2. The self-assembling growth process of this material is also investigated preliminarily.